Product Quality, Promotion on Purchase Decisions Through Price Discounts As An Intervening Variable: (Case Study At Toko Cindur Batik Batam) - Sri Ekowati Budi Rahayu; Tibrani Tibrani; Widodo Ismanto (Amkop Management Accounting Review (AMAR), 2026)
The increasing use of price–discount–oriented promotional strategies presents both opportunities and challenges for Toko Cindur Batik Batam in enhancing promotional effectiveness and adapting to a competitive market environment. This study aims to examine the influence of product quality and promotion on purchasing decisions, with price discounts acting as an intervening variable. A quantitative research approach was employed, utilizing Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique to test the proposed hypotheses and analyze the relationships among variables. Data were analyzed using SmartPLS, with the measurement model specified as reflective and the structural model evaluated through multiple path relationships. The results indicate that product quality and promotion collectively explain a substantial proportion of purchasing decision behavior, while price discounts play a significant mediating role in strengthening purchasing decisions. The findings further suggest that periodic, competitive price discount strategies, when supported by product differentiation and perceived added value, can effectively influence consumer purchasing decisions. This study contributes to marketing strategy literature by emphasizing the importance of integrating pricing incentives with product value creation to sustain competitiveness in the retail batik industry.